Upaya Pendidikan Kesehatan Untuk Meningkatkan Pengetahuan Keluarga Tentang Resiko Jatuh Pada Pasien Hipertensi - Sholati, Roisna Apik, Abi Muchlisin, S.KM., M.Kep, Supratman, M.Kep, Ph.D (2017)
There are several types of infectious diseases, non-communicable diseases and chronic illnesses. One non-communicable diseases are becoming a very serious health problem today is hypertension. Genesis falls themselves can occur and is a fatal occurrence that is not recognized by someone with hypertension who are conducting activities and may result in loss of consciousness, stroke or physical weakness. Knowledge family to family members who suffer from hypertension is very important .. Authors are able to apply and add to the knowledge and experience regarding cases of hypertension in the community and keluarga.Metode is descriptive case study approach that is guided by the scientific method Nursing Process include: Assessment, Data analysis, Diagnosis, Intervention, Implementation, and Evaluasi.Setelah given 8x family of nursing actions during the 60 minute meeting, a family willing and able to care for the sick keuarga hypertension properly. The success of the nursing process family will be achieved when every member of the cooperative in continuing nursing process, then the family is willing and able to change the bad habits that can harm health and all acts of family nursing that have been granted in accordance with the care plan such as progressive relaxation, gymnastics hypertension and delivery of education health in theory and in research can reduce pain.